Is There a Global Carbonate Layer in the Oceanic Mantle?. Issue 2 (20th January 2021) - Hammouda, T.; Manthilake, G.; Goncalves, P.; Chantel, J.; Guignard, J.; Crichton, W.; Gaillard, F.
Abstract: Previous modeling of carbonate subduction by high‐pressure experimentation has allowed to propose scenarios for bulk carbon return to the mantle, but the detailed transfer mechanisms have seldom been studied. We monitored carbonate–silicate reactions by combining high‐pressure experiments and synchrotron‐based X‐ray diffraction. Carbonates break down at moderate pressure and high temperature and CO2 is trapped at grain boundaries. Further isothermal compression yields melting, which may control continuous carbon introduction, first in the mantle wedge, and next, away from the wedge. Carbon presence has been discussed in a variety of magmatic contexts, under the oceanic lithosphere (hotspots, petit spots, and fossil ridges). We suggest the presence of a global carbon‐rich layer under the oceanic lithosphere that is steadily fed by subduction processes. This layer can be the source of mechanical weakening of the lithosphere–asthenosphere boundary under the oceans. Therefore, carbon‐induced compression melting may be a key mechanism of modern‐style plate tectonics. Plain Language Summary: Plate tectonics, the mechanism by which rigid plates migrate atop the Earth's mantle, necessitate mechanical decoupling between the plates (lithosphere) and the underlying mantle (asthenosphere). The presence of a melt layer acting as a lubricating agent has been discussed on the basis of geophysical evidence, such as provided by seismic and electrical conductivity data analysis. In this study, we show that this layer can be fueled by the melting of carbonate‐rich material carried down by oceanic plates returning to the mantle at subduction zones. This process is continuous because the Earth is an active planet with permanent seismic and volcanic activity. It may have been going on for billions of years and may have been fundamental for the initiation of plate tectonics. Key Points: CO2 release during subduction and its transfer to the mantle initiates compression melting at the lithosphere–asthenosphere boundary Dissolution–precipitation‐driven melt porous flow results in migration of carbonatite melt away from the mantle wedge Steady supply of carbonated material by subduction may build up a global carbonatite melt layer at the top of the oceanic asthenosphere